Vanished! - Ponti, James (Ponti, James. Framed! novel, 2018)
In Washington, D.C., twelve-year-old Florian Bates, a consulting detective for the FBI, and his best friend Margaret must uncover the truth behind a series of private middle school pranks that may or may not involve the daughter of the President of the United States.